The Effect of Airbnb on Hotel Performance: Comparing Single- and Multi-Unit Host Listings in the United States. (August 2022) - Dogru, Tarik; Mody, Makarand; Line, Nathan; Hanks, Lydia; Suess, Courtney; Bonn, Mark
Extant research provides ample evidence that Airbnb has an adverse impact on hotel revenues and that a majority of Airbnb hosts offer multiple listings on the platform. Arguably, multi-unit host listings are the primary driving force for the associated decreases in hotel revenues. To test this proposition, this study examines the extent to which single- and multi-unit host Airbnb host listings have differing effects on hotel revenues. The results show that the adverse impact of Airbnb supply on hotel revenues was mainly driven by decreases in hotel prices rather than decreases in hotel demand. Contrary to expectations, single-unit host listings exerted greater downward pricing pressure on hotels than multi-unit host listings. These effects were consistently observed across hotel segments, with economy-scale hotels experiencing substitution effects in addition to pricing pressure. The findings have significant implications for researchers and stakeholders impacted by the sharing economy in the lodging industry.